Job Search Behaviour and Time Preferences: Evidence from the Netherlands - Thomas M. van Huizen; Janneke Plantenga (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2013)
This paper examines theoretically and empirically the effects of time preferences on job search behaviour of the unemployed. The aim of the study is to test the exponential versus the hyperbolic discounting model within a labour market context. The theoretical relations between patience on the one hand and job search intensity, reservation wages and the exit rate to employment on the other hand depend on whether exponential or hyperbolic discounting is assumed. Assessing these relations empirically therefore provides a test of the two alternative models of discounting. We make use of the DNB Household Survey, a large Dutch longitudinal survey containing various indicators of job search effort, reservation wages and detailed information on individual time preferences. The results are in line with the hyperbolic discounting model.
Keywords: 330; time preferences; unemployment; job search; Hyperbolic discounting